The Correlation Number Of Parity On Third Trimester Of Pregnancy To Anxiety In Confronting Birth Labour - Susanti, Susanti; Sari, Ika Novita (Jurnal Midpro, 2020)
Anxiety is a condition that experiencing anxious, fear that followed by somatic symptoms to inform there was hyperactivity in autonomy neural system. Number of parity is one of factor that emerge anxiety in pregnancy. The aim of this study to find out the correlation number of parity on third trimester of pregnancy to anxiety in confronting birth labor phase in BPM Walladatun Islah A.MKeb Batu Aji. The design of this study was used cross sectional which is independent variable and dependent variable was taken in the same time. The population of samples are 71 pregnancy mothers (read: respondents) Â in their third trimester in working area of BPM Walladatun Islah A.MKeb Batu Aji, and method of sampling was simple random sampling. The instrument of this study was using questionnaire that was spread around August to September 2019. The data analyze was using Personal Chi Square. The result is 50 pregnancy mother with primigravid, there is 1 respondent with no anxiety symptom (2,0%), 20 respondents (40,0%) with mild anxiety, and 10 respondents (20,0%) with moderate anxiety, 16 respondents (32,0%) severe anxiety, and 3 respondents (6.0%) very severe anxiety. WhereasÂ  21 respondents with multigravida , which is one respondent with no anxiety at all (4,8%), 16 respondents ( 76,2%) with mild anxiety, and 2 respondents (9,5%) with moderate anxiety, one respondent (4,8%) with severe anxiety, and one respondent (4,8%) with very severe anxiety. The analyze of Chi Square was shown of p-value 0,44 (p<0,05). The conclusion there is a correlation number of parity on third trimester to anxiety in confronting birth labor in BPM Walladatun Islah A.MKeb Batam City in 2019.